If It's Not Shamanic, Is It Sham? An Examination of Media Responses to Woodland School Art - Blundell, Valda; Phillips, Ruth (Anthropologica, 2022)
This paper examines media responses to both "Woodland School" painting and that of its founder, Norval Morrisseau. Reactions of the media, museums and galleries, and their confusing classifications of Woodland School art as both ethnographic material and modern art are assessed. Two dominant themes in media treatment of Woodland School art, the survivalistic and the revivalistic, are identified. Finally, the ways these responses misrepresent the intended meanings and goals of the artists are discussed.